Just the Right Amount of Ethics Inspires Creativity: A Cross-Level Investigation of Ethical Leadership, Intrinsic Motivation, and Employee Creativity - Feng, Jie (Journal of business ethics, 2018)
Based on ideology-infused psychological contract theory and cognitive evaluation theory, this study investigated the curvilinear relationship between ethical leadership and employee creativity. A curvilinear mediation model was proposed to explain the impact of ethical leadership on creativity, using employee intrinsic motivation as the mediator. Applying a two wave sampling design that consist 258 employees and their leaders, we found that employee creativity improved as ethical leadership increased from low to moderate levels. However, the employee creativity improvement was attenuated when ethical leadership increased from moderate to high levels. Furthermore, the study also revealed that employee intrinsic motivation partially mediated this curvilinear relationship. The theoretical and managerial implications are discussed.